2021
DOI: 10.1186/s40703-021-00142-7
|View full text |Cite
|
Sign up to set email alerts
|

Analytical solutions and 3D numerical analyses of a shallow tunnel excavated in weak ground: a case from Turkey

Abstract: Due to the increasing population and resulting transportation needs, the number of subway and high-speed railway projects has also increased. The geometric constraints of such projects have caused many tunnels to be built in weak ground. Thus, weak ground tunnelling has attracted the attention of tunnel engineers and researchers. The main purposes of this study are to analyse the T4 tunnel excavated in weak ground and to compare the results obtained from the analytical solutions and 3D numerical analyses. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…For this reason, both squeezing and swelling potential are the most important factors in tunnels excavated in weak rocks and soils. Two different tunnel support system approaches are used for tunnels excavated in weak rocks and soils [19][20][21][22]. These are called the passive method and the active method.…”
Section: Weak Rock Tunnelling-soil Tunnellingmentioning
confidence: 99%
“…For this reason, both squeezing and swelling potential are the most important factors in tunnels excavated in weak rocks and soils. Two different tunnel support system approaches are used for tunnels excavated in weak rocks and soils [19][20][21][22]. These are called the passive method and the active method.…”
Section: Weak Rock Tunnelling-soil Tunnellingmentioning
confidence: 99%
“…Nevertheless, due to the assumptions of numerical simulations, the degree of reduction of actual working conditions is low. Numerical simulations thus have a higher error, so numerical simulation technology is mostly used to verify the actual results [21,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, when examining the geological conditions of complex areas such as karst development, various safety accidents such as collapses [1] and runoff water [2] can easily be triggered, affecting all stakeholders as well as those not directly involved in the project [3]. Several case studies reported worldwide [4][5][6][7][8] suggest that uncertainties in the geology and complexity of tunnel construction processes often result in construction delays and cost overruns [9][10][11][12]. Travertines from Plio-Quaternary are exposed in the vast area around the Antalya region.…”
Section: Introductionmentioning
confidence: 99%